The squirels who squabbled - Bright, Rachel; Field, Jim (London orchard books, 2017)
Greedy squirrels Cyril and Bruce both have their sights on a very special prize: the very last nut of the season! As the nut bounces crazily though the forest, the squirrels race after it, between the trees, over boulders, down the river and - ARGH! - right to the edge of a waterfall! Working together might be the only way to save themselves now
English stories
Keywords: Squirrels Juvenile fiction; English stories